A Therapeutic Efficacy of Shirodhara in Ayurveda: A Review Study - Sharma, Ravi; Rai, Girish Narain; Parida, Akhilanath (International Research Journal of Ayurveda & Yoga, 2022)
Introduction-Shirodhara is the application of medicinal Kwatha (Decoction) or oil to the forehead. According to Ayurveda, Shirodhara is an example of BahyaSnehana, or external oleation therapy. The primary indications for Shirodhara are neurological and psychosomatic illnesses. Stress is a big part of today’s modern lifestyle, which makes it difficult for people to go about their daily lives. The most prevalent and difficult conditions in the modern period include conditions like insomnia, headaches, facial paralysis, scalp psoriasis, hair loss, etc. However, there hasn’t been any efficient management of these complaints up to this point. Determining safe and efficient treatment techniques for these disorders is therefore urgently needed. Thus, an effort is made to rule out Shirodhara’s effectiveness in treating various psychological disorders. Methods-review is collected from classics, commentaries etc.,Results-This procedure’s apparent mode of action are unclear. Ayurveda focused more on the results of the method than its action. Discussion-Treat the scalp with medicated oil in such a way that the oil remains in contact with the scalp for a certain period of time called MurdhaTail. In order to better understand Shirodhara, a review of the Samhita, Chikitsa Grantha, Nighantus, and Ayurvedic texts was done. During the study, Shirodhara’s indications, contraindications, and therapeutic efficacy were noted.